Development of new functional nanocomposites based on graphene quantum dots supported metal/metal oxide nanoparticles for electrochemical biosensing of DNA/RNA molecules - Victor - Lazaras; Vinoth (2023)
3 Goal 1C: Synthesis of graphene quantum dots supported metal and metal oxide nanocomposites TOTAL Using an eco-friendly approach, the GQDs-NPs composite material were synthesized.GQDs were added into the NPs solution in order to achieve 1:0.5 to 1:12 ratio of NPs: GQDs (typically 0.1-3 nM GQDs concentration) into the final solution under ultrasonication using a QUAVA ultrasonic mini reactor (kaijo, Japan). Sonication of the reaction medium will result in the generation of a large amount of shear forces by cavitation which will help to anchor the GQDs on nanoparticles surface. 4 Goal: 2 To assess the influence of synthesized pristine graphene quantum dots and pristine metal/metal oxide nanoparticles on electrochemical detection of DNA/RNA sensing. TOTAL Textural and chemical composition of prepared pristine materials were characterized by BET analysis, XRD, FT-IR, UV-vis, Raman, TGA/DTA, and XPS. Morphological changes of MNPs and MONPs were investigated by SEM, TEM, AFM, SAED and EDS analyses. Electrochemical responses of pristine GQDs and metal/Metal oxide NPs were evaluated by cyclic voltammogram, and impedance spectroscopy. Electrochemical performances of the prepared pristine GQDs and metal/Metal oxide NPs toward sensing of DNA/RNA molecules were evaluated by cyclic voltammogram, differential pulse voltammogram, linear sweep voltammogram, square wave voltammograms, chronoamperometric analysis. 5 Goal: 3 To assess the influence of synthesized graphene quantum dots supported metal and metal oxide nanocomposites on electrochemical detection of DNA/RNA sensing using screen-printed electrodes. TOTAL Textural and chemical composition of synthesized graphene quantum dots supported metal and metal oxide nanocomposites were characterized by BET analysis, XRD, FT-IR, UV-vis, Raman, TGA/DTA, and XPS. Morphological changes of GQDs supported metal/Metal oxide nanocomposites were investigated by SEM, TEM, AFM, SAED and EDS analyses. Electrochemical responses of GQDs supported metal/Metal oxide nanocomposites were ...